2006
DOI: 10.1111/j.1439-0329.2006.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on anastomosis groups of Rhizoctonia solani isolates causing disease in two forest nurseries in Poland

Abstract: Thirty-eight isolates of Rhizoctonia spp. were isolated from Scots pine (Pinus sylvestris) seedlings with damping-off symptoms, originating from two forest nurseries in central-west Poland (Wronczyn and Jarocin) and from diseased seedlings grown in soil from Wronczyn nursery. Majority of these isolates (79%) had multinucleate cells and were identified as Rhizoctonia solani. The remaining isolates were recognized as binucleate Rhizoctonia spp. R. solani isolates were characterized using hyphal anastomosis and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…Differences in aggressiveness was observed among isolates of AG 2‐1 towards endive; on lettuce and carrot not only AG 2–1 isolates, but also isolates of several other AGs differed in aggressiveness. This observation was previously reported for several AGs in combination with a specific crop and in particular for AG 2‐1 isolates (Schneider et al ., 1997b; Stepniewska‐Jarosz et al ., 2006; Woodhall et al ., 2007). The present study also confirmed the pathogenic characteristics of some AGs, as already described, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in aggressiveness was observed among isolates of AG 2‐1 towards endive; on lettuce and carrot not only AG 2–1 isolates, but also isolates of several other AGs differed in aggressiveness. This observation was previously reported for several AGs in combination with a specific crop and in particular for AG 2‐1 isolates (Schneider et al ., 1997b; Stepniewska‐Jarosz et al ., 2006; Woodhall et al ., 2007). The present study also confirmed the pathogenic characteristics of some AGs, as already described, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There is thus a need to assess the properties of plant nursery networks in a number of representative regions and for various pathogens and endophytes (e.g. Stanosz et al ., 2005; Giménez‐Jaime et al ., 2006; Menkis et al ., 2006; Pinto et al ., 2006; Stepniewska‐Jarosz et al ., 2006). This need is immediate wherever nurseries have been tested positive for the presence of Phytophthora ramorum , the causal agent of sudden oak death (e.g.…”
Section: Potential Implications For Plant and Forest Pathologymentioning
confidence: 99%
“…The most severe pathogens causing damping-off in Polish forest nurseries include species from genera: Fusarium, Rhizoctonia, Pythium, Alternaria and Cylindrocarpon [3,[5][6][7][8]. Fungi belonging to the Rhizoctonia genus represent a wide range of pathogenic, non-pathogenic and mutualistic species [9].…”
Section: Introductionmentioning
confidence: 99%
“…Fungi belonging to the Rhizoctonia genus represent a wide range of pathogenic, non-pathogenic and mutualistic species [9]. Most studies on this group of fungi, known to attack more than 200 different species of plants, relate to agricultural plants, while only few researchers have studied this group of organisms in forest nurseries [4,6,[10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%